Larval Fish Assemblages and Distribution Patterns in the Zhongsha Atoll (Macclesfield Bank, South China Sea) - Huang, Delian; Chen, Jing; Xu, Lei; Wang, Xuehui; Ning, Jiajia; Li, Yafang; Wang, Lianggen; Liu, Shuangshuang; Lin, Zhaojin; Du, Feiyan (Frontiers in Marine Science, 2022)
The remote coral reef in the deep sea is one of most important nursery grounds for many marine fishes in the South China Sea. Diversity studies on larval fishes in this area are few and the information on the coral reefs’ fish ecosystem is lacked. In this study, larval fishes were sampled during the summer of 2019 from the Zhongsha Atoll in the South China Sea and identified using DNA barcodes for the first time. Totally 95 species of larval fishes were recognized, belonging to 37 families and 12 orders based on morphological classification and the DNA barcoding identification. Most of the larval fish collected could be assigned to three categories as reef-associated, deep-sea and pelagic, respectively. Most of the species were small fish lack of commercial, but would play an important role in coral reef ecosystem. Nonetheless, some commercial fishes including Auxis thazard, Euthynnus affinis, Sarda orientalis Decapterus macarellus, Lutjanus viridis and Centropyge vrolikii were dominate species higher than 2% total catch. The larval fish assemblage was identified distinct spatial differences responding well with the geographical conditions. The most reef-associated fish occurred inside the Atoll and the abyssal fish presented near the edge. In addition, larval fish spread over from the southwest to northeast, may suggesting in reflect the oceanography effect.